Prothrombin complex concentrate for doac-associated intracerebral hemorrhage: First case report from Vietnam - Phuong, Dao Viet; Ton, Mai Duy; Anh, Nguyen Hoang; Hung, Vuong Hoang; Dung, Nguyen Tien; Anh, Nguyen Minh; Viet, Bui Quoc (Tạp chí Nghiên cứu Y học, 2026)
Intracerebral hemorrhage (ICH) associated with direct oral anticoagulants (DOACs) is a life-threatening condition with a high risk of hematoma expansion. In settings where specific reversal agents such as andexanet alfa are unavailable, 4-factor prothrombin complex concentrate (4F-PCC) is commonly used as an alternative for urgent coagulation reversal. We report a 56-year-old man receiving rivaroxaban who presented with acute left thalamic intracerebral hemorrhage (baseline hematoma volume 3.6 mL). On admission, his international normalized ratio (INR) was 1.55 and anti-factor Xa level was 201.3 ng/mL. 4F-PCC was administered at a dose of 25 IU/kg (total 1,500 IU) at 5.7 hours after symptom onset (door-to-PCC time: 102 minutes). Thirty minutes after infusion, INR decreased to 1.28, with subsequent reduction in anti-Xa activity. Follow-up CT at 24 hours showed no hematoma expansion. No thromboembolic complications were observed. The patient achieved a favorable functional outcome (modified Rankin Scale score of 2) at discharge. This case illustrates the feasibility of 4F-PCC for early coagulation reversal in DOAC-associated ICH in a resource-limited setting. However, given the small hematoma volume and single-case design, the contribution of 4F-PCC to clinical outcome should be interpreted with caution.